Active With Whom? Examining the Social Context of Physical Activity in Individuals After Stroke and Their Partners - Pauly, Theresa; Ashe, Maureen C.; Murphy, Rachel; Gerstorf, Denis; Linden, Wolfgang; Madden, Kenneth M.; Hoppmann, Christiane A. (Frontiers in Public Health, 2021)
Engaging in regular moderate-to-high intensity physical activity (MVPA) is crucial to reduce future health risk for individuals living with the effects of a stroke and their partners. Although numerous studies point to the importance of social factors in physical activity engagement, little is known about with whom individuals after stroke and their partners engage in physical activity with and whether different physical activity companions are uniquely associated with MVPA. Eighty-nine community-dwelling individuals after stroke (Mage = 68.64, SD = 10.44; 74% male) and 83 partners (Mage = 66.04, SD = 9.91; 24% male) completed 14 consecutive days of daily life assessments that included wearing physical activity monitors (accelerometers) and self-reporting physical activity companions (n = 1,961 days). Results show that average levels of MVPA were correlated between partners (r = .38), as were day-to-day MVPA fluctuations (r = .34). Importantly, for individuals after stroke, being active with their partner, but not with any other physical activity companion, was linked with elevated daily MVPA. In contrast, for partners of individuals after stroke, engaging in physical activity with a variety of different companions (partner, other family member, friend, colleague) was each associated with higher MVPA in daily life. For both individuals after stroke and their partners being active by oneself (without a companion) on a given day was not associated with elevated MVPA. Findings suggest that interventions that promote physical activity engagement should consider the role of meaningful others, with the partner being particularly key for individuals living with chronic health conditions.